Comparison of food waste using the PDAT and comstock methods in inpatients in Bengkulu - Repa Ghina Sonia; Betty Yosephin Simanjuntak; Desri Suryani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Food waste is an indicator of the quality of hospital nutritional services. A high percentage of waste indicates low patient intake and may affect the nutritional status and recovery. This study was conducted in May 2025 at Harapan Dan Doa Hospital, Bengkulu City, in the Safa, Marwah, and Mina wards, where food waste exceeded the standard (<20%). This study aimed to compare the Pictorial Dietary Assessment Tool (PDAT) and Comstock methods for measuring patient food waste. A descriptive cross-sectional design was applied to 50 inpatients selected through accidental sampling method. Data were collected through observation using both methods. The Mann-Whitney test was used to analyze differences, and sensitivity and specificity were assessed using cross-tabulation. The results showed no significant differences between the two methods across all food categories (p > 0.05). PDAT was considered more accurate because it uses photographs of meals before and after consumption, making the assessment more objective. Meanwhile, Comstock relies on visual estimates, which may introduce bias. Both methods had high sensitivity (>80%), indicating good agreement. In conclusion, the PDAT and Comstock tools are suitable for evaluating patient food waste and monitoring the quality of nutrition services in hospitals.